NEGATIVE INTEREST RATES AS AN INSTRUMENT OF MONETARY POLICY - Maistrenko, Oleksii; Maistrenko, Svistlana (Socio-economic relations in the digital society, 2020)
The paper introduces a study about the possibility of application of negative interest rates by central banks of developed countries as an instrument of monetary policy. This article highlights the importance and effectiveness of this method in terms of overcoming the crisis in the economy, stimulating market rates, maintaining exchange rate stability, and promoting economic growth. Despite the limited number of scientific works, here summarized provisions of world economists and best practices on the Negative Interest Rate Policy. This policy was introduced in Sweden, England, Switzerland, Denmark, Japan, Austria, Finland and Germany. The authors indicated that implementation of the Negative Interest Rate Policy method gave positive trends: better quality of loans; an increased volume of intermediation; flexible financial conditions that support demand and price stability. The paper describes negative impact of Negative Interest Rate Policy as well. Mostly it concerns net interest margin and banks profitability, focused on retail deposits and other economic processes. The ethical and psychological aspect of the Negative Interest Rate Policy indirectly affects the level of confidence in the banking system as a whole. Especially in case of the introduction of negative interest rates on deposits by commercial banks. The paper defines a range of perspective measures necessary for Ukraine to stimulate monetary influence. The existing imbalances in the economy shows that traditional instruments of monetary regulation are not sufficiently effective for Ukraine. Negative Interest Rate Policy actions will help to reduce the cost of credit resources, increase their availability. Structural adjustment of cash flows for the process of implementation will improve economic activity.